Clinical significance of the tumor microenvironment in non-small cell lung cancer - Shimizu, Katsuhiko (AME Publishing Company, 2013)
Several biomarkers have been reported as predictors of survival and recurrence in non-small cell lung cancer. Recently, several groups have demonstrated that the immune microenvironment of the primary tumors is a prognostic factor. These “immunological biomarkers” in the tumor microenvironment are useful predictors of prognosis as well as promising targets for novel therapeutic approaches. Especially, tumor-infiltrating Treg cells are a powerful immunological biomarker, and possible mechanisms involved in the induction of tumor-infiltrating Treg cells are the expression of Cox-2, IL-12Rβ2 or the lack of IL7R on the tumor cells. These findings may pave the way for individualized immunomodulatory therapies to deplete tumor-infiltrating Treg cells from the tumor microenvironment.